Penerapan Metode Imprest dalam Pengelolaan Kas Kecil untuk Operasional Harian pada Umkm Es Iso Lego - Putri Imeldatus Sholeha; Siti Amaliyah; Jihan Bintang Angely; Sri Rahayuningsih (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the implementation of the imprest method in petty cash management to enhance the effectiveness of daily operations at the micro, small, and medium enterprise (MSME) Es Iso Lego, located in Rungkut Madya, Surabaya. The research is motivated by common issues among MSMEs that still apply simple petty cash systems without fixed balances, leading to inaccurate records and weak financial control. This study employed a descriptive qualitative approach using a case study method. Data were collected through direct interviews with the business owner, observation of daily operational activities, and documentation of purchase receipts and digital financial records. The findings reveal that the petty cash system at Es Iso Lego has not fully applied the imprest method principles, as the cash balance remains fluctuating and is not maintained consistently. Although each expenditure is supported by receipts, the recording process lacks systematic structure. The results imply that applying the imprest method is essential to improve efficiency, accountability, and internal control in MSME financial management. A fixed-balance petty cash system with proper documentation enables business owners to better monitor daily expenses and ensure financial transparency.